ҚАРАҚАЛПАҚ ТАРИЙХЫЙ ҚОСЫҚЛАРЫНЫҢ ИЗЕРТЛЕНИЛИЎИ - Турдыев, Б. (ILIM hám JÁMIYET, 2022)
The article covers several periods in the development and formation of Karakalpak historical songs. Folklore, combined with genres, covers all periods of the political and social life of the Karakalpak people. Historical songs arose and developed in all periods, depending on the way of life of the people.